Ecological awareness of Generation Z through academic literature and interdisciplinary perspectives - Khayru, Rafadi Khan; Issalillah, Fayola; Darmawan, Didit; Mardikaningsih, Rahayu (Proceeding of International Management Conference and Progressive Papers, 2025)
Generation Z grows up amidst a massive flow of information, making them a group that is highly connected to global issues, including environmental sustainability. This study aims to systematically review the development of ecological awareness among this generation using a literature review approach. The analysis was conducted on various academic sources discussing how information, social values, educational experiences, and digital media influence the ecological attitudes and actions of Generation Z. The study results indicate that awareness of environmental issues among the younger generation has increased, but it has not yet fully manifested in consistent behavior. The discrepancy between the values believed and actual actions is still found in various forms. Factors such as social pressure, emotional narratives, concrete experiences, and social identity have a significant contribution to the formation of ecological attitudes. Therefore, strategies to enhance environmental awareness in this generation must be designed through an approach that simultaneously touches on emotional, cognitive, and social realms. This study is expected to provide a theoretical and conceptual foundation for formulating more effective environmental education and communication policies that align with the characteristics of the current generation.